Investigating a new framework for the impact of parenting styles on aggressive behaviours among primary school students - Zhu, C. L. (Serials Publications, 2017)
This research wascarried out to investigate a new framework for the impact of parenting styles on primary school students' aggressive behaviours. The research focused on the aspects of factors, perception, implications and problems related to parenting styles and investigated how parenting styles can be applied to manage the aggressive behaviours of primary school students. To obtain data for this study, questionnaires were distributed in four primary schools in Johor. A total of 169 respondents were completed. The data was analysed using SPSS software. The results indicated that the proposed framework can be effective in the management of aggressive behaviours of primary schools students. The results also demonstrated that the new framework has the potential to change traditional parenting styles into more interactive parenting styles.